Returning Cotton Stalks to the Field Increases Residual Plastic Film in Oasis Agroecosystems under Long‐term Mulched Drip Irrigation. Issue 5 (1st September 2019) - Zhang, Jinzhu; He, Huaijie; Wang, Zhenhua; Fan, Bihang; Zheng, Xurong; Li, Wenhao; Lin, Henry; Guo, Li
Abstract : Core Ideas: Residual plastic film (RPF) was measured in cotton fields following varied years of mulched drip irrigation. The amount of large RPF pieces >30 cm 2 (or 50–100 mg) at 0 to 15 cm increased by 20% (or 10%) after cotton stalks were returned. Small film fragments accumulated in the tillage layer as the number of years of drip mulching increased. Returning cotton stalks to the field benefits yield, but strongly impacted the amount and distribution of RPF. The difficult recovery of RPF should be taken into account for ensuring sustainable oasis agriculture and reducing soil pollution. After the long‐term practice of dripping irrigation under plastic film (also called mulched drip irrigation) in Xinjiang, efficient recovery of the residual plastic film (RPF) becomes a grand challenge. This is especially true for cotton fields where RPF amount has significantly exceeded China's National Standard and caused severe soil pollution. Here, we examined the RPF in cotton fields in a typical oasis agroecosystem in Xinjiang with different lengths of time of mulching practice (5, 9, 11, 13, 15, and 19 yr). We documented the amount and distribution of the RPF at 0‐ to 40‐cm depth via six field sampling events in 2016 and 2017, before and after cotton stalks were returned to the field. The density of the RPF of six sampling plots in 2016 was 121.85, 215.85, 250.63, 294.17, 327.83, and 352.38 kg ha −1, rising from 5 to 19 yr of mulched drip irrigation, which further increased by 18.92, 16.75, 16.59, 17.82, 19.25, and 16.95 kg ha −1 in 2017. As years of mulching increased, small RPF fragments accumulated in the tillage layer due to low efficient recovery of the film. In addition, returning cotton stalks to the field intensified the downward movement of RPF to deeper soil depths. The amount of large RPF of 30 cm 2 per piece in the 0‐ to 15‐cm soil depth increased by 20% after cotton stalks were returned to the field; those of weight 50 to 100 mg per piece similarly increased by 10%. The fragmentation and accumulation of larger RPF pieces at depth could further challenge film recovery. To mitigate the soil pollution problems caused by the RPF and to ensure the sustainable development of the oasis agriculture, biodegradable film or thicker plastic film are suggested as an alternative of the thin plastic film in mulching practice.